2014
DOI: 10.1074/jbc.m114.557561
|View full text |Cite
|
Sign up to set email alerts
|

Release of Interleukin-1α or Interleukin-1β Depends on Mechanism of Cell Death

Abstract: Background: Cell death is a regulator of inflammation via the master cytokine IL-1.Results: Apoptotic stimuli induced a caspase-8-dependent release of IL-1β from macrophages. Necroptotic stimuli induced a calpain-dependent release of IL-1α.Conclusion: Mechanisms of cell death dictate the nature and form of IL-1 release.Significance: Sterile inflammatory responses may be determined by the mechanisms of cell death potentially allowing for selective interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
116
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 139 publications
(124 citation statements)
references
References 39 publications
6
116
0
2
Order By: Relevance
“…141,[177][178][179] Moreover, extracellular ATP promotes the activation of the NLR family, pyrin domain containing 3 (NLRP3) inflammasome in APCs, hence stimulating the processing and release of interleukin (IL)-1b and IL-18. 119,[180][181][182][183][184][185][186][187][188][189] In line with this notion, the immunogenic potential of cells succumbing to ICD can be significantly reduced by pharmacological or genetic interventions that limit the availability of ATP in the pericellular space, such as the administration of recombinant apyrase (an ATP-degrading enzyme) or the transfection-enforced overexpression of ectonucleoside triphosphate diphosphohydrolase 1 (ENTPD1, best known as CD39), which converts ATP into ADP and AMP. 190 Intriguingly, CD39 and 5 0 -nucleotidase, ecto (NT5E, best known as CD73), which transforms AMP into adenosine, are often overexpressed by malignant tissues.…”
Section: Immunogenic Cell Death Signalingmentioning
confidence: 82%
“…141,[177][178][179] Moreover, extracellular ATP promotes the activation of the NLR family, pyrin domain containing 3 (NLRP3) inflammasome in APCs, hence stimulating the processing and release of interleukin (IL)-1b and IL-18. 119,[180][181][182][183][184][185][186][187][188][189] In line with this notion, the immunogenic potential of cells succumbing to ICD can be significantly reduced by pharmacological or genetic interventions that limit the availability of ATP in the pericellular space, such as the administration of recombinant apyrase (an ATP-degrading enzyme) or the transfection-enforced overexpression of ectonucleoside triphosphate diphosphohydrolase 1 (ENTPD1, best known as CD39), which converts ATP into ADP and AMP. 190 Intriguingly, CD39 and 5 0 -nucleotidase, ecto (NT5E, best known as CD73), which transforms AMP into adenosine, are often overexpressed by malignant tissues.…”
Section: Immunogenic Cell Death Signalingmentioning
confidence: 82%
“…A common theme amongst IL-1a-eliciting stimuli is that they trigger lytic cell death (e.g. necrosis, pyroptosis, necroptosis), indicating that passive release during cell lysis is a major mechanism for IL-1a release [44]. Such a model explains the previously puzzling profile of IL-1a release by inflammasome agonists; Gross and co-workers showed that while IL-1b release by a range of NLRP3 agonists is fully NLRP3/ASC/caspase-1 dependent, IL-1a release is NLRP3/ASC/caspase-1-dependent upon cell stimulation with some NLRP3 agonists (nigericin, ATP, Candida) but partially or fully NLRP3/ASC/caspase-1-independent for others (the particulate or crystalline compounds, alum, TiO2, silica, monosodium urate crystals) [22].…”
Section: Passive Release Of Alarmins: Il-1a and Il-33mentioning
confidence: 99%
“…10,34 Although a reason for this specificity currently is unknown, a possible reason could be the nature of cell death perturbed in each autoinflammatory disorder. 9 Although necrotic cell death releases bioactive IL-1a, IL-1b requires caspase-1e and/or caspase-8emediated maturation and release. Thus, depending on the type of cell death that is instigated, either IL-1a or IL-1b could initiate and promote sterile inflammation, driving the disease pathogenesis.…”
Section: Discussionmentioning
confidence: 99%